2016
DOI: 10.1007/s13205-015-0337-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic purity in rice (Oryza sativa L.) hybrids using microsatellite markers

Abstract: The objective of the present study is to detect genetic impurity in the seed lots of CMS lines, restorers and hybrids and to identify signature markers to differentiate parents and hybrids through DNA-based assays. Furthermore, attempts have been made to find out an alternative to Grow-Out-Test, which is very tedious, time consuming and used conventionally for seed genetic purity testing since beginning of quality seed multiplication chain. Fifty-one rice-specific sequence tagged microsatellite (STMS) primer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 19 publications
2
32
0
Order By: Relevance
“…The former, which is relied on the different phenotypic traits of hybrids and their parental lines, is considerably restricted for the limited intuitive agronomical traits, or because some agronomical traits can be detected only in the particular plant growth period, and some traits are very vulnerable to the environmental conditions. The assessment of genetic purity of hybrids via molecular fingerprinting or banding patterns of their parental lines based on SSR markers have been utilized in some crops, such as in maize (Hipi et al, 2013), rice (Bora et al 2016), and barley (Ben Romdhane et al, 2018). In our present study, the similar banding patterns (Figure 3) as Ben Romdhane et al (2018) were observed in the true hybrids, which are co-dominant SSR markers from both parents.…”
Section: Discussionsupporting
confidence: 83%
“…The former, which is relied on the different phenotypic traits of hybrids and their parental lines, is considerably restricted for the limited intuitive agronomical traits, or because some agronomical traits can be detected only in the particular plant growth period, and some traits are very vulnerable to the environmental conditions. The assessment of genetic purity of hybrids via molecular fingerprinting or banding patterns of their parental lines based on SSR markers have been utilized in some crops, such as in maize (Hipi et al, 2013), rice (Bora et al 2016), and barley (Ben Romdhane et al, 2018). In our present study, the similar banding patterns (Figure 3) as Ben Romdhane et al (2018) were observed in the true hybrids, which are co-dominant SSR markers from both parents.…”
Section: Discussionsupporting
confidence: 83%
“…These analyses were made on many plant species, such as Ambrosia artemisiifolia [36], Vigna unguiculata L. Walp. [37], Brassica oleracea [38], Solanum tuberosum [39], and Oryza sativa L. [40], and demonstrated the versatility of microsatellite markers. The number of SSR markers for the opium poppy is increasing, but they are poorly characterized in most cases; therefore, only a few of them are suitable for variety identification.…”
Section: Introductionmentioning
confidence: 90%
“…The SSR markers identified had both female and male specific bands and are useful in genetic purity testing. The use of SSR markers for genetic purity testing has already been demonstrated in maize (Daniel et al, 2012;Mrutu, 2015;Simon and Lovasz, 2016;Wu et al, 2010); rice (Bora et al, 2016;Galal et al, 2014;Moorthy et al, 2011;Sudharani et al, 2013), pearl millet (Nagawade et al, 2016), eggplant (Reddy et al, 2015), soybean (Zhang et al, 2014), cauliflower (Zhao et al, 2012) and in sunflower (Pallavi et al, 2011).…”
Section: Resultsmentioning
confidence: 99%